2021
DOI: 10.1007/s13204-021-01693-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gold, platinum, and gold-platinum alloy nanoparticle colloids with high-power megahertz-repetition-rate lasers: the importance of the beam guidance method

Abstract: Nanoparticles of noble metals and their alloys are of particular interest for biomedicine and catalysis applications. The method of laser ablation of bulk metals in liquids gives facile access to such particles as  high-purity colloids and is already used in industrial research. However, the method still lacks sufficient productivity for industrial implementation into series production. The use of innovative laser technology may help to further disseminate this colloid synthesis method in the near future. Ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 56 publications
2
50
0
Order By: Relevance
“…Note that the EDX‐mapping pixel intensity is not linearly correlated with the composition, a pixel is displayed where the elemental threshold count rate is exceeded, showing homogeneous elemental distribution in the particle volume but no direct quantitative information. Such solid‐solution structure has been reported earlier for laser‐generated AuPt particles [25–27] …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Note that the EDX‐mapping pixel intensity is not linearly correlated with the composition, a pixel is displayed where the elemental threshold count rate is exceeded, showing homogeneous elemental distribution in the particle volume but no direct quantitative information. Such solid‐solution structure has been reported earlier for laser‐generated AuPt particles [25–27] …”
Section: Resultssupporting
confidence: 81%
“…Such solid-solution structure has been reported earlier for laser-generated AuPt particles. [25][26][27] In addition, we prepared a 98 : 2 (Au : Pt) atomic mixture target and EDX-analysis of this target verified the 98 : 2 atomic ratio (Figure 1B). The Pt content in the nanoparticles fabricated from these targets was too low to be verifiably measured via EDX.…”
Section: Resultsmentioning
confidence: 81%
“…Specifically, full lateral pulse separation is necessary to avoid a reduction in nanoparticle yield caused by pulse shielding. This point has been addressed in a recent report by the Barcikowski group [139].…”
Section: Fabrication Of Plasmonic Nanoparticles By Pulsed Laser Ablat...mentioning
confidence: 93%
“…Materials exposed to a laser flux absorb the incident laser energy, turning the material to plasma. Laser ablation of solid metal has problems with aggregation and inadequate degradation, therefore in previous studies many researchers have shown generation of PtNPs by PLAL (pulsed laser ablation in liquid) ( Waag et al, 2021 ; Fedorova et al, 2020 ; N Madlum et al, 2021 ). The milling process involves gradually decreasing the particle size and mixing them into new phases ( Jan et al, 2021 ; Mathew et al, 2021 ).…”
Section: Ptnps Preparation Methodsmentioning
confidence: 99%